SCREENÄ°NG AND OPTÄ°MÄ°ZATÄ°ON OF CULTURE MEDÄ°A FOR CHLORELLA SP.AS A RAW MATERIAL FOR BÄ°ODÄ°ESEL PRODUCTÄ°ON - AMİT KUMAR SHARMA and PRADEEPTA KUMAR SAHOO and SHAİLEY SİNGHAL (International Journal of Pharma and Bio Sciences, 2015)
Alga biomass based biofuels seems to be the most promising renewable fuels for the future. However, large scale algae cultivation is mandate for industrial biofuel production. Before going to large scale, screening and media optimization is necessary for low-cost microalgae biofuels, as media composition significantly affect the microalgal growth, lipid yield, and microalgae biodiesel cost. This investigation studied the effect of different media i.e Blue green-11(BG-11), Bold basal medium, Fog’s medium and Basal medium on microalgae growth and lipid productivity. Out of them, BG-11 medium was observed best for biodiesel production with higher lipid yield. Furthermore, algae cultivation in one liter polybag and 7 liter capacity photobioreactor under outdoor condition was also carried out using BG-11 as a grwoth medium. Additinally,.different lipid extraction method tested with biomass of Chlorella sp. using ethanol, methanol, hexane and a mixture of chloroform: methanol. Among the tested methods, the mixture of chloroform:methanol (2:1) was most effective, extracting an average of 15% of total lipids. Lipid profiles of Chlorella sp. were compared with Jatropha biodiesel in the percentage of saturated and unsaturated fatty acids; however, Chlorella sp. have more poly-unsaturated fatty acids such as linoleic (C18:2) and linolenic (C18:3) acids than Jatropha oil. Biodiesel produced by transesterification of Chlorella sp. satisfies international Physico-chemical standard parameters such as Cetane number, Saponification value, Iodine value and Degree of unsaturation.